Mini mysteries : 34 tricky tales to untangle - Walton, Rick; Kote, Genevieve (Middleton, WI : American Girl, 2015)
Contains 34 stories for readers to solve. The solutions can be found by lifting the flaps on the back pages of the book.
"American Girl."
Ages 8 and up.
8+.
Keywords: Detective and mystery stories; Lift-the-flap books -- Specimens; Mystery and detective stories; Lift-the-flap books; Toy and movable books; Detective and mystery stories